THE EFFECT OF GENERATIONS ON LEARNING TECHNOLOGY AND MANAGEMENT MODELS USED IN OPERATIONS (Third Sector Social Economic Review, 2021)
During the third industrial revolution (Industry 3.0), enterprises started to use automation technologies in their production facilities using programmable logic controllers (PLC), developed their management models such as total quality management (TQM), lean manufacturing, six sigma, material requirement planning (MRP), and enterprise resource planning (ERP), and invested in internet and digital technologies. During the fourth industrial revolution (Industry 4.0); Internet of Things (IoT), augmented reality, simulation, big data, cloud computing, horizontal and vertical system integration, additive manufacturing (3D printers), cybersecurity and autonomous robots have been developed. In the study, it has been investigated whether the Industry 3.0 and Industry 4.0 technologies are affected by the personality traits of generations. According to the results of multinominal logistic regression method, there are statistically significant differences between generations. In addition, the personality traits of neuroticism, negative value, and openness to experience are effective in learning the mentioned technologies.
Keywords: Industry 3.0; Industry 4.0; Generations; Key Personality Traits